Theory and Practice of Business Process Management - David Tuček (European Financial and Accounting Journal, 2009)
Traditional model of management is based on hierarchical decomposition of organizational structure. Company is divided on workroom, union, partitions and every formation of his has independent agenda and his responsibility. However the formations often have tendency create about themselves barrier, especially communications and informatics barrier. Compared to that, process management is relatively new view of organization that moves activities of many companies. Process organization tries organizing and managing the work like comprehensive complex, which is of further distributed on individual sub-processes, which are logically linked. It is known; that the BPM is exploited in many line productions, nonproductive and tertiary sphere and his conventions pays in the same way in all lines. This statement I can corroborate thanks to my research results (below). Within the overall context of this research, we have understood the aspects of BPM to mean: a view and standpoint on the problems and issues related to the management of enterprises` processes and this includes such areas as aims, factors, components, support as well as the benefits of BPM itself. As it was indicated in the title of this paper, we mainly concentrate here on presenting the main results of the last-mentioned research area, i.e. where we evaluate the benefits of PM from the managements of Czech enterprises` point-of-view. The results are shown as a summary of all of the companies (respondents), of which there were 132.
Keywords: O31; 650; Business Process Management; Process Modeling; Business Process Reengineering; ARIS (Architecture of Integrated Information Systems); ARIS Toolset; ARIS Business Architect; ERP (Enterprise Resource System)